Persistent Functional Decline Following Hospitalization with Influenza or Acute Respiratory Illness. Issue 3 (8th December 2020) - Andrew, Melissa K.; MacDonald, Sarah; Godin, Judith; McElhaney, Janet E.; LeBlanc, Jason; Hatchette, Todd F.; Bowie, William; Katz, Kevin; McGeer, Allison; Semret, Makeda; McNeil, Shelly A.
Abstract : Background/objectives: Influenza is associated with significant morbidity and mortality, particularly for older adults. Persistent functional decline following hospitalization has important impacts on older adults' wellbeing and independence, but has been under‐studied in relation to influenza. We aimed to investigate persistent functional change in older adults admitted to hospital with influenza and other acute respiratory illness (ARI). Design: Protective observational cohort study. Setting: Canadian Immunization Research Network Serious Outcomes Surveillance Network 2011 to 2012 influenza season. Participants: A total of 925 patients aged 65 and older admitted to hospital with influenza and other ARI. Measurements: Influenza was laboratory‐confirmed. Frailty was measured using a Frailty index (FI). Functional status was measured using the Barthel index (BI); moderate persistent functional decline was defined as a clinically meaningful loss of ≥10 to <20 points on the 100‐point BI. Catastrophic disability (CD) was defined as a loss of ≥20 points, equivalent to full loss of independence in two basic activities of daily living. Results: Five hundred and nineteen (56.1%) were women; mean age was 79.4 (standard deviation=8.4) years. Three hundred and forty‐six (37.4%) had laboratory‐confirmed influenza. Influenza cases had lower baseline function (BI = 77.0 vs 86.9, P < .001) and higher frailty (FI = 0.23 vs 0.20, P < .001) than those with other ARI. A total of 8.4% died, 8.2% experienced persistent moderate functional decline, and 9.9% experienced CD. Higher baseline frailty was associated with increased odds of experiencing functional decline, CD, and death. The experience of functional decline and CD, and its association with frailty, was the same for influenza and other ARI. Conclusion: Functional loss in hospital is common among older adults; for some this functional loss is persistent and catastrophic. This highlights the importance of prevention and optimal management of acute declines in health, including influenza, to avoid hospitalization. In the case of influenza, for which vaccines exist, this raises the potential of vaccine preventable disability.